(untitled) (Международный научный журнал «Инженер», 2026)
The article presents the results of studies of the physico-chemical processes of forming the structure of the material and the development of effective compositions of modified gypsum-carbonate composite gypsum materials based on gypsum binder, microcalcite and modifying polymer additives, contributing to the improvement of their rheological and physico-mechanical properties and, accordingly, to increase the bending strength of building decorative ceiling suspended gypsum boards based on them. As a result, it became possible to organize the production of ceiling-mounted suspended composite gypsum boards with high water resistance and physico-mechanical properties and low cost, as well as the widespread use of this board in the construction of residential buildings and construction structures in the republic